Canine and Human Dirofilariosis in the Rostov Region (Southern Russia). (23rd December 2010) - Kartashev, Vladimir; Batashova, Irina; Kartashov, Sergey; Ermakov, Alexey; Mironova, Anna; Kuleshova, Yulia; Ilyasov, Boris; Kolodiy, Irina; Klyuchnikov, Alexander; Ryabikina, Elena; Babicheva, Marina; Levchenko, Yulia; et al.
Abstract : Epidemiological data on canine and human dirofilariosis in the Rostov Region (Southern Russia) are presented. Prevalence of Dirofilaria spp. infections in 795 autochthonous dogs, assessed by the Knott test, was 20.25%. The highest prevalence was found in Novocherkassk (38.3%) and Rostov-on-Don (18.5%), while prevalences were lower in other points of the region. Prevalence of D. repens was 44.7%, prevalence of D. immitis was 30.3%, and coinfections were observed in 25.0% of the dog population. A case finding study carried out during 9 years (2000–2009) revealed 131 cases of human dirofilariosis in the Rostov Region, 129 of subcutaneous dirofilariosis and 2 of pulmonary dirofilariosis. Seroprevalence among 317 healthy blood donors from the Rostov Region was 10.4%, while seroprevalence in policemen living in Rostov city and working in training dogs was 19%. These data show high infection rates of Dirofilaria spp. in both human and dog populations of Rostov, probably because of the existence of favorable conditions for the transmission in this region.